Hydrogel Inverse Replicas of Breath Figures Exhibit Superoleophobicity Due to Patterned Surface Roughness - Arora, Jaspreet Singh (Langmuir : the ACS journal of surfaces and colloids, 2016)
The wetting behavior of a surface depends on both its surface chemistry and the characteristics of surface morphology and topography. Adding structure to a flat hydrophobic or oleophobic surface increases the effective contact angle and thus the hydrophobicity or oleophobicity of the surface, as exemplified by the lotus leaf analogy. We describe a simple strategy to introduce micropatterned roughness on surfaces of soft materials, utilizing the template of hexagonally packed pores of breath figures as molds. The generated inverse replicas represent micron scale patterned beadlike protrusions on hydrogel surfaces. This added roughness imparts superoleophobic properties (contact angle of the order of 150° and greater) to an inherently oleophobic flat hydrogel surface, when submerged. The introduced pattern on the hydrogel surface changes morphology as it swells in water to resemble morphologies remarkably analogous to the compound eye. Analysis of the wetting behavior using the Cassie-Baxter approximation leads to estimation of the contact angle in the superoleophobic regime and in agreement with the experimental value